Analisis Wacana Kritis Pemberitaan People Power pada Media Jawa Pos dan Republika Edisi Mei 2019 - Laili Zulfa (Al-MUNZIR, 2022)
This study focuses on news on people power in the online media Jawa Pos and Republika May 2019 edition. The research method used is Critical Discource Analaysis which refers to the perspective of Norman Fairclough. The results showed that: the production of people power news texts on republika tended to be negative. While the production of people power news text in Jawa Pos tends to be positive. The consumption of the text of the People's Mind is the reader perceives the same (negative) with the production of texts made by the People's Mind. Whereas the consumption of the text of Republika is the opposite (negative) reader with the production of texts made by Jawa Pos that the news tends to be positive.Kata kunci: people power, Norman Fairclough, Discourse.